1978
DOI: 10.1007/bf00426631
|View full text |Cite
|
Sign up to set email alerts
|

Lithium prevention of amphetamine-induced ?manic? excitement and of reserpine-induced ?depression? in mice: Possible role of 2-phenylethylamine

Abstract: Repeated treatment of mice with lithium chloride (45 mg/kg, i.p., daily for 8 days) reduced the jumping, fighting, stereotypies, and hyperactivity induced by d-amphetamine (5 mg/kg, i.p.). Lithium also reduced the hypoactivity observed 1--3 h after reserpine (0.75 mg/kg, i.p.). In biochemical studies we found that 8-day treatment with lithium markedly reduced (to 45% of control) the recovery from brain of labelled 2-phenylethylamine (PEA) following i.p. injection of labelled L-phenylalanine, while decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…In 1971, Cox et al (1971) reported that lithium attenuated stimulant-induced hyperlocomotion in rats. This effect was later reported in mice (Berggren et al, 1978;Borison et al, 1978). Because the administration of dopaminergic stimulants to rodents induces a characteristic increase in activity, and because this activity is attenuated by lithium administration, the hyperlocomotion model may provide insight into the clinical endophenotype described above.…”
Section: Introductionmentioning
confidence: 81%
“…In 1971, Cox et al (1971) reported that lithium attenuated stimulant-induced hyperlocomotion in rats. This effect was later reported in mice (Berggren et al, 1978;Borison et al, 1978). Because the administration of dopaminergic stimulants to rodents induces a characteristic increase in activity, and because this activity is attenuated by lithium administration, the hyperlocomotion model may provide insight into the clinical endophenotype described above.…”
Section: Introductionmentioning
confidence: 81%
“…While exceptions in the literature exist, they can often be attributed to an inappropriate dose of either amphetamine or lithium. As mentioned above, a decrease in hyperlocomotion is often concomitant with a rise in stereotypy at higher doses of amphetamine; this fact is likely the reason why Ebstein and colleagues found no effect of lithium on amphetamine-induced hyperlocomotion in rats, as they used doses of amphetamine ranging from 5 to 15mg/kg, the lowest of which is itself a dose high enough to elicit considerably stereotypy (Borison et al, 1978;Ebstein et al, 1980;Fessler et al, 1982). At this elevated dose, stereotypy was likely to be a confounding factor in the measure of hyperlocomotion.…”
Section: The Effect Of Lithium On Amphetamine-induced Hyperlocomotionmentioning
confidence: 99%
“…Such automatic methods have the advantage of eliminating subjectivity over observer-based scoring common prior to technological advances. Indeed, some data have been acquired using observation alone to evaluate hyperlocomotion, often making use of rating scales which allow the rater to evaluate locomotor activity and stereotypy simultaneously (Borison et al, 1978;Fessler et al, 1982).…”
Section: The Effect Of Lithium On Amphetamine-induced Hyperlocomotionmentioning
confidence: 99%
See 2 more Smart Citations